INCOME ANALYSIS OF AGROINDUSTRI BANANA SALE IN CIAMIS REGENCY - Yuda Yulian; Trisna Insan Noor; Muhammad Nurdin Yusuf (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Banana is one of the agricultural commodities whose existence is abundant and widely spread throughout Indonesia which can be processed into various derivative products, one of which is banana sale. This study aims to analyze the income of banana sale agroindustry in Ciamis Regency. The research was designed using a qualitative descriptive method with the type of case study on banana sale agroindustry in Margajaya Village, Sukadana District as one of the centers of banana sale production in Ciamis Regency. The data analyzed were primary data obtained through interviews using previously prepared questionnaires. The analysis used includes the analysis of costs, revenues, and revenues. The results showed that the total cost incurred by the banana sale agroindustry was 4,146,500, - and received an income of Rp 6,000,000, - so that an income of Rp 1,853,500, - was obtained in one production process.